1984
DOI: 10.1172/jci111241
|View full text |Cite
|
Sign up to set email alerts
|

Encainide and its metabolites. Comparative effects in man on ventricular arrhythmia and electrocardiographic intervals.

Abstract: As bstract. To assess the relative contributions of encainide and its putatively active metabolites, O-demethyl encainide (ODE) and 3 methoxy-O-demethyl encainide (3MODE), to the drug's pharmacologic effects, we compared intravenous infusions and sustained oral therapy in two phenotypically distinct groups of patients, extensive and poor metabolizers ofencainide. Unlike poor metabolizers, extensive metabolizers had appreciable quantities of both metabolites detectable in plasma and had fourfold shorter elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Thus, the parent drug accumulates with the result that pharmacological effects, such as arrhythmia suppression and QRS prolongation, are seen (Carey et al 1984).…”
Section: Encainide Disposition In Healthy Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the parent drug accumulates with the result that pharmacological effects, such as arrhythmia suppression and QRS prolongation, are seen (Carey et al 1984).…”
Section: Encainide Disposition In Healthy Subjectsmentioning
confidence: 99%
“…Interestingly, encainide, ODE and MODE produce qualitatively different electrophysiological changes. In most studies, ODE is a more potent depressor of sodium channels and cardiac conduction (evidenced in patients by QRS widening) than either encainide or MODE (Carey et al 1984;Fain et al 1986). However, MODE is more potent than encainide or ODE in prolonging ventricular refractoriness in dogs (Fain et al 1986) and QT interval in humans (Barbey et al 1986), and unlike encainide and ODE, does not raise energy requirements for defibrillation in dogs (Fain et al 1986).…”
Section: Encainide Disposition In Healthy Subjectsmentioning
confidence: 99%
“…The other 10% produce very little or no ODE or MODE, but produce measurable amounts of third metabolite, N-desmethyl encainide (NDE). All of these metabolites possess potent class 1 antiarrhythmic actions of their own (Carey et al, 1984;Davy et al, 1986;Barbey et al, 1988). Because they have longer elimination half-lives than encainide, MODE and ODE tend to accumulate in the plasma of patients on chronic oral therapy and reach concentrations well in excess of the parent compound (Kates et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Because they have longer elimination half-lives than encainide, MODE and ODE tend to accumulate in the plasma of patients on chronic oral therapy and reach concentrations well in excess of the parent compound (Kates et al, 1982). Furthermore, it has been suggested that ODE in particular, may contribute significantly to the clinical effects of encainide (Carey et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In a minority of patients (approximately 7% of caucasians and blacks), the specific hepatic cytochrome P450 responsible for encainide O-demethylation is functionally absent on a genetic basis.14,l5 In such "poor metabolizers,," encainide clearance is markedly reduced, ODE plasma concentrations are low, MODE is not detected in plasma, and encainide itself accumulates to antiarrhythmic concentrations. [14][15][16] Many drugs, including the antihypertensive debrisoquin, have been used as probes for the presence of this cytochrome, termed P450dbl. [17][18][19] We have previously shown that the metabolism of ODE to MODE is dependent on the same genetic polymorphism as that controlling encainide O-demethylation.13 Thus, long-term administration of ODE to patients with the poor metabolizer phenotype might lead to undesirable accumulation of this very potent sodium channel blocker.…”
mentioning
confidence: 99%